An Incorporated Use of Fuzzy Logic Toolbox and Modelica Library to Design SSSC Damping Controller - Boonrat Somritvanitcha; Issarachai Ngamroo; Komsan Hongesombut (My University, 1970)
ObjectStab is a general purpose simulation tool for power system stability studies developed by Modelica which is an object-oriented modeling language. It provides enough modeling flexibility to allow addition or modification of new power system components. This paper describes an incorporated use of fuzzy logic toolbox in Matlab/Simulink and Object-Stab library to enhance the application of this library into fuzzy control design environment. The example provided here is the modeling of the static synchronous series compensator (SSSC) which is the new device developed in the ObjectStab. In addition, the interface of ObjectStab with Matlab/Simulink for an SSSC damping controller design by fuzzy logic toolbox is explained step by step. Simulation studies in a multi-machine power system confirm the effectiveness of the designed fuzzy controller.
Keywords: Modelica; Toolbox; Interface (matter); Modeling and Simulation Systems